Manejo de la hipertensión arterial en niños y adolescentes: recomendaciones de la Sociedad Europea de Hipertensión - Lurbe, Empar; Cifkova, R.; Cruickshank, J. K.; Dillon, M. J.; Ferreira, I.; Invitti, C.; Kuznetsova, T.; Laurent, S.; Mancia, G.; Morales-Olivas, F.; Rascher, W.; Redon, J.; et al. (Anales de pediatría, 2010)
Hypertension in children and adolescents has been gaining ground in cardiovascular medicine, mainly due to the advances made in several areas of pathophysiological and clinical research. These guidelines arose from the consensus reached by specialists in the detection and control of hypertension in children and adolescents. Furthermore, these guidelines are a compendium of scientific data and the extensive clinical experience it contains represents the most complete information that doctors, nurses and families should take into account when making decisions.
Gesehen am 19.04.2023